Bilateral thalamic infarction due to artery of percheron occlusion with corresponding CT perfusion abnormalities. (3rd June 2015) - MacLellan, A; Boyle, K
Abstract : Background: The Artery of Percheron (AOP) is a rare anatomic variant that supplies the bilateral medial thalami from a common origin; occlusion results in a characteristic pattern of bilateral thalamic infarction seen on neuroimaging. To date, we have not identified any cases in the literature describing corresponding ischemic changes seen on hyperacute CT Perfusion imaging. We aimed to characterize perfusion abnormalities seen in AOP occlusion by describing a case presentation, highlighting the importance of recognizing this syndrome clinically, and radiologically, in an acute stroke presentation. Methods: Description of a case, and literature search on PubMed. Results: A 74-year-old man was seen in the ER as a Code Stroke protocol with acute alteration of level of consciousness (LOC). ER assessment showed no focal abnormalities and was significant only for disorientation. CT/CTA/CTP initially appeared unremarkable for acute abnormalities. His LOC deteriorated requiring intubation, and subsequent MRI showed bilateral thalamic infarction. Further CT Perfusion review demonstrated increased Mean Transit Time and decreased Blood Flow without Volume abnormalities in the bilateral paramedian thalami. Conclusion: AOP infarction is an uncommon cause of bilateral thalamic infarction. We have demonstrated a case highlighting perfusion abnormalities not previously reported in AOP occlusion, illustrating the importance and utility of advanced CT perfusion imaging whilst considering less common stroke syndromes.